2014
DOI: 10.1007/s10899-014-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling Among Ontario Students: Associations with Substance Abuse, Mental Health Problems, Suicide Attempts, and Delinquent Behaviours

Abstract: This paper describes gambling problems among Ontario students in 2009 and examines the relationship between gambling problems and substance use problems, mental health problem indicators, and delinquent behaviors. Data were derived from the Ontario Student Drug Use and Health Survey of Ontario students in grades 7-12. Gambling problems were measured as 2 or more of 6 indicators of problem gambling. In total 2.8% of the students surveyed endorsed two or more of the problem gambling items. The odds of problem ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 48 publications
2
49
0
3
Order By: Relevance
“…Examples of shared risk factors for both gambling and substance use include family history, mental health problems, and gender (Barnes et al, 1999; Cook et al, 2015; Mezzich et al, 2001; Vitaro et al, 2014). A recent study utilizing adolescent twin pairs found a significant genetic influence on both gambling and substance use (Vitaro et al, 2014), which is consistent with other research among adults (Slutske et al, 2000; Slutske et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of shared risk factors for both gambling and substance use include family history, mental health problems, and gender (Barnes et al, 1999; Cook et al, 2015; Mezzich et al, 2001; Vitaro et al, 2014). A recent study utilizing adolescent twin pairs found a significant genetic influence on both gambling and substance use (Vitaro et al, 2014), which is consistent with other research among adults (Slutske et al, 2000; Slutske et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A score of 3 or more out of 12 was considered to demonstrate significant delinquency (Cook et al 2015). The six questions measuring a potential gambling problem were taken from the South Oaks Screen Revised for Adolescents (SOGSRA) (Winters et al 1993).…”
Section: Delinquency Gambling and Scholastic Achievementmentioning
confidence: 99%
“…The six questions measuring a potential gambling problem were taken from the South Oaks Screen Revised for Adolescents (SOGSRA) (Winters et al 1993). Adolescents scoring two or more out of the six items were classified as having a gambling problem (Cook et al 2015). Finally, scholastic achievement was measured by a self-reported response to the question, BOn average, what marks do you usually get in school?,^with the following options: 90-100%, 80-89%, 70-79%, 60-69%, 50-59%, or below 50%.…”
Section: Delinquency Gambling and Scholastic Achievementmentioning
confidence: 99%
“…So berichteten etwa Cook et al (2015) (Meyer und Fabian 1992). Personen, die illegale Handlungen bejahten, zeigten zudem exzessiveres und problematischeres Spielverhalten, hatten mehr psychosoziale Probleme infolge des Spielens und zogen gleichzeitig mehr subjektive Befriedigung aus dem Spielen.…”
Section: Neurobiologische Grundlagenunclassified